Investigation of angiogenesis genes with anterior cruciate ligament rupture risk in a South African population. Issue 5 (4th March 2018) - Rahim, Masouda; Hobbs, Hayden; van der Merwe, Willem; Posthumus, Michael; Collins, Malcolm; September, Alison V.
ABSTRACT: The angiogenesis-signalling pathway is a physiological response after mechanical loading to promote matrix remodelling and thereby maintain tissue homeostasis. Studies have shown increased expression of angiogenic molecules in response to loading and in ruptured ligaments. Recently, polymorphisms within the vascular endothelial growth factor A ( VEGFA ) and kinase insert-domain receptor ( KDR ) genes were associated with risk of anterior cruciate ligament (ACL) ruptures and Achilles tendinopathy in Caucasian study groups. A case-control genetic association study was conducted on 100 controls and 98 participants with surgically-diagnosed ACL ruptures; of which 51 participants reported non-contact mechanism of injury (NON). All participants were genotyped for five functional polymorphisms: VEGFA (rs699947, rs1570360, rs2010963) and KDR (rs2071559, rs1870377). Haplotypes were inferred. In the male participants, the KDR rs2071559 AG genotype was significantly over-represented ( P = 0.048, OR: 1.90, 95% CI: 1.00–3.59) in the controls. Furthermore, the GG genotype was significantly under-represented in the male controls compared to the male ACL group ( P = 0.018, OR: 2.77, 95% CI: 1.17–6.55) and the male NON subgroup ( P = 0.013, OR: 3.26, 95% CI: 1.24–8.58). Haplotype analysis implicated the KDR gene in all participants and in male participants separately. Collectively, these results implicate the angiogenesis-signalling pathway as a potentially key biological pathway contributing to ACL injury susceptibility.